NATIONAL AUDIT OF SEIZURE MANAGEMENT IN HOSPITALS 2 (NASH2). Issue 10 (9th September 2014) - Marson, Tony; Dixon, Pete; Pearson, Mike
Abstract : Background: NASH1 (National Audit of Seizure management in UK Hospitals) collected data in 2011 and fed back in 2012. It identified significant shortfalls and variability in the way that care was provided. Here we report the second round–NASH2. Methods: NASH2 assessed the prior, immediate, and onward care of patients attending Emergency Departments with seizures. Sites provided anonymous data on 30 consecutive cases via a web-based database between June and September 2013. Results: Data were collected from over 4, 500 patients across 154 sites in the UK (mean age=47.1, 57% male). Results show considerable inter-site variability, with a few sites performing well to show good care is possible. Assessment on arrival was again inadequate, a proper neurological examination with plantar responses recorded in 34% (IQR 20.0–43.3), an attempt to gain an eyewitness description in 69% (IQR 60.0–83.3), and an ECG performed in 75% (IQR 65.9–86.7). Only 55% of first seizure patients were referred for any form of neurology specialist assessment, and less than half for known epilepsy. 45% had a previous attendance in the last 12 months. Conclusions: Findings confirm unacceptable variability in the provision of care. Commissioners, primary, secondary and tertiary care, and the public must work together to commission and deliver better services.